PENGARUH PENGETAHUAN HIJAU, NORMA SUBJEKTIF, DAN KEPEDULIAN LINGKUNGAN TERHADAP NIAT BELI PRODUK RAMAH LINGKUNGAN - Puspa Ningrum, Kumala; Manalu, S. Rouli; Setyabudi, Djoko (Interaksi Online, 2024)
The emergence of environmentally friendly lifestyle trends and environmentally conscious consumption patterns increases people's purchasing intentions or desires to purchase environmentally friendly products. This research aims to determine the influence of the variables green knowledge, subjective norms, and environmental concern on the variable intention to purchase environmentally friendly products. The theory used in this research is the Theory of Reasoned Action. The population used in this research is Generation Z and Millennials in the age range 17 – 40 years. Hypothesis testing was carried out using multiple linear regression analysis using SPSS software. The research results show that green knowledge, subjective norms, and environmental concern simultaneously influence the intention to purchase environmentally friendly products with a significance value of 0.000 <0.05, which means very significant. Apart from that, the coefficient of determination (R Square) shows a value of 0.537, which means that green knowledge, subjective norms and environmental concern have a 53.7% influence on the intention to buy environmentally friendly products. Therefore, the research results are in line with the theory used in this research that attitudes or behavior and subjective norms can predict the emergence of buying intentions in a person